2014
DOI: 10.1080/07294360.2014.956698
|View full text |Cite
|
Sign up to set email alerts
|

Student skills and the Bradley agenda in Australia

Abstract: This paper investigates the study strategies that first-year Australian university students bring with them to university. The research has currency due to the implementation of the Review of Australian higher education [Bradley, D., Noonan, P., Nugent, H., & Scales, B. (2008). Review of Australian higher education: Final report. Canberra: Australian Government.], which recommended that universities increase the number of students in undergraduate courses. In response to government incentives to increase enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…As in the present study, in Bartalo and Guimarães (2008) as well as in Ribeiro and Silva (2007) research, no significant differences emerged when examining the results of LASSI in relation to age. This result differed from those obtained by Carpenter et al (2014)) and Braten and Olaussen (1998) who found that older students significantly outperformed younger students on LASSI attitude scale.…”
Section: Discussioncontrasting
confidence: 99%
“…As in the present study, in Bartalo and Guimarães (2008) as well as in Ribeiro and Silva (2007) research, no significant differences emerged when examining the results of LASSI in relation to age. This result differed from those obtained by Carpenter et al (2014)) and Braten and Olaussen (1998) who found that older students significantly outperformed younger students on LASSI attitude scale.…”
Section: Discussioncontrasting
confidence: 99%
“…Students in the fourth-year cohort started their occupational therapy course in 2012, the first cohort to be admitted to the course after the Australian federal government uncapped tertiary admission numbers by allowing universities to admit students based on demands for specific academic courses. Carpenter et al (2015) considered this group of students to be unique and found that students in this cohort lacked sufficient skills to cope with university level studies. In addition, 60.7% of students in the fourth-year cohort started the occupational therapy course directly from high school, a much higher proportion than those in the first year (51.2%), second year (49.4%) and third year (46.6%) year-level cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…However, there may be a cultural difference in approaches to study, which means that results from Lawson (2014) and Richardson (2010) cannot be generalized into the Australian context. Results from the current study suggest that it may be useful to routinely evaluate approaches to study among incoming occupational therapy students to identify their strengths and weaknesses in study skills, as Carpenter et al. (2015) did, so as to put appropriate strategies in place to facilitate a deep approach to study.…”
Section: Implications and Recommendationsmentioning
confidence: 93%
“…The Bradley Report (2008), a report commissioned by the Australian Government to assist in the development of a model of education for the next decade, identified first-in-family generational status as one of the barriers to higher education in Australia. Part of this report led to the implementation of strategies which improved the opportunities for university participation for Australians (Carpenter et al, 2015). Strategies included funding to universities for many academic and school to university linkage programs.…”
Section: Bridging the Gapmentioning
confidence: 99%